Percepción local acerca de la calidad del agua y la herpetofauna en fincas ganaderas del municipio de Matiguas, Nicaragua - Gómez Martínez, Mario J. (2014)
Perceptions of livestock producers regarding their welfare, water quality and herpetofauna diversity were examined using semistructured interviews with farmers and local institutions. Interviews was used to develop indicators framed in community capitals and validated through four workshops. The results indicated that producers have similar perceptions of the relationships between water quality and biodiversity. Producers indicated that the amount of water has been declining, although most producers do not perceive a relationship between water quality, human health or livestock health. There was a significant absence of: local institutions, biodiversity conservation projects promotion and financing, access and water storage. Regarding the herpetofauna, the’ responses of producers have focused on medicinal, nutritional functions and biological regulation that these organisms provide. Most farmers interviewed stated that the incorporation ogf agroforestry systems on offers benefits including improved water quality and conservation of agricultural biodiversity. Farmers demonstrated local knowledge in locating water sources and in the traditional use of herpetofauna.